Culture Supernatants of the Cyanobacterium Trichormus Sp. Promote the Growth of the Grass Polypogon Australis Brong: Role of P and Mn - Wilkens-Anwandter, M; Ortiz-Calderon, C; Pontigo-Gallardo, D (Elsevier B.V., 2023)
The potential of some soil cyanobacteria to influence plant development through the release of biologically active substances has been extensively characterized. The use of cyanobacterial culture supernatants is among the strategies for this purpose, as they contain compounds that can influence plant development. However, there is little information on how the remaining nutrients from the culture medium used, could contribute to the effect observed in the treated plants. In the present work, Trichormus sp., a native Chilean cyanobacterium isolated from drylands whose supernatants improved the cumulative germination and the shoot and root growth of the native grass Polypogon australis, was selected. The observed effects were significant when compared with water as a control but did not significantly differ when the BG-11 nutrient medium was used as a control. The nutrient content of Trichormus sp. supernatants was characterized throughout the growth phases of the culture on BG-11 medium, showing an important decrease in P (100 %) and Mn (84 %) content after the late exponential phase. Based on these results, a P and Mn-free BG-11 medium (BG-11 M) was prepared. In a bioassay with P. australis, the BG-11 M effect was compared with Trichormus sp. supernatants, which contained 40 % of P and 46 % of Mn with respect to the original BG-11 medium. The results showed that the BG-11 M was less effective in promoting the shoot growth of P. australis than the supernatants, indicating that both elements, P and Mn, have a role in the development of P. australis. We emphasize the need to consider the composition of nutrients remaining on the culture medium when evaluating the effects of cyanobacterial cultures on plant growth and development. © 2023 Elsevier B.V.